2014
DOI: 10.2527/jas.2013-6861
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of immunologically castrated (with Improvest) barrows (with or without ractopamine) compared to gilt, physically castrated barrow, and intact male pigs

Abstract: The study used a randomized complete block design (blocking factor was date of start on test) with 5 treatments: 1) physically castrated barrows (PC), 2) intact males (IM), 3) gilts (G), 4) immunologically castrated barrows (IC), and 5) immunologically castrated barrows fed ractopamine at 5 mg/kg (IC+RAC). The study used 192 pigs and was performed from the 16 wk of age (67.2 ± 2.52 kg BW) to a pen mean BW of 132.5 ± 3.60 kg. For IC+RAC, ractopamine was fed for the final 23 d of the study. Pigs were housed in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
8
12
0
Order By: Relevance
“…These steroids have anabolic effects that stimulate muscle and bone growth, nitrogen and phosphorus retention, and cause a redistribution of nutrients, resulting in better feed conversion, lower backfat thickness and increased lean tissue of intact male carcasses compared to castrates or females (Squires, 2011). In this study, in the time period from the second immunization dose at d 137 to d 164, there was no increase in ADFI of immunocastrated pigs, which was reported by Puls et al (2014). However, other authors (Rikard-Bell et al, 2009;Fàbrega et al, 2010) have reported an increase in ADFI in immunocastrated males.…”
Section: Animal Performancesupporting
confidence: 58%
“…These steroids have anabolic effects that stimulate muscle and bone growth, nitrogen and phosphorus retention, and cause a redistribution of nutrients, resulting in better feed conversion, lower backfat thickness and increased lean tissue of intact male carcasses compared to castrates or females (Squires, 2011). In this study, in the time period from the second immunization dose at d 137 to d 164, there was no increase in ADFI of immunocastrated pigs, which was reported by Puls et al (2014). However, other authors (Rikard-Bell et al, 2009;Fàbrega et al, 2010) have reported an increase in ADFI in immunocastrated males.…”
Section: Animal Performancesupporting
confidence: 58%
“…Several studies have evaluated growth performance among the 4 sexes under group-housing conditions (Fábrega et al, 2010;Weiler et al, 2013;Puls et al, 2014). Since this was a metabolism experiment, pigs were housed individually.…”
Section: Growth Performancementioning
confidence: 99%
“…Diets fed during the study were similar to those described by Puls et al (2014) and were formulated to meet the nutrient requirement of intact males as proposed by NRC (2012). Briefly, diets were based on corn and soybean meal and did not contain ethanol coproducts.…”
Section: Animals Housing and Dietsmentioning
confidence: 99%